1986
DOI: 10.1523/jneurosci.06-11-03205.1986
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of synaptic terminals in lamina II and Clarke's nucleus after unilateral lumbosacral dorsal rhizotomy in adult cats

Abstract: Evidence from previous light-microscopic studies suggested that lumbosacral dorsal rhizotomy in cats elicits sprouting of converging undamaged systems into partially deafferented Clarke's nucleus and lamina II. We therefore applied quantitative electron-microscopic methods to determine whether this sprouting is associated with replacement of synaptic terminals (reactive reinnervation). We used stereological and morphometric methods to estimate terminal number per cross section in right and left lamina II and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
30
0

Year Published

1996
1996
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(32 citation statements)
references
References 47 publications
2
30
0
Order By: Relevance
“…Although there is evidence that deafferentation results in compensatory sprouting of surviving sensory neurons (Murray and Goldberger, 1986;Goldberger and Murray, 1988), several studies using WGA-HRP have found little indication of sprouting of C-fiber primary sensory afferents out of their normal termination zone into neighbouring denervated areas of spinal cord, unless the denervation is accompanied by a conditioning peripheral nerve lesion (Molander et al, 1988;LaMotte et al, 1989;McMahon and Kett-White, 1991;Florence et al, 1993). There are reports, however, that after deafferentation produced by pronase injection into the sciatic nerve, true collateral sprouting of apparently uninjured saphenous central terminals occurs into the neighbouring sciatic nerve terminal territory (LaMotte et al, 1989;LaMotte and Kapadia, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Although there is evidence that deafferentation results in compensatory sprouting of surviving sensory neurons (Murray and Goldberger, 1986;Goldberger and Murray, 1988), several studies using WGA-HRP have found little indication of sprouting of C-fiber primary sensory afferents out of their normal termination zone into neighbouring denervated areas of spinal cord, unless the denervation is accompanied by a conditioning peripheral nerve lesion (Molander et al, 1988;LaMotte et al, 1989;McMahon and Kett-White, 1991;Florence et al, 1993). There are reports, however, that after deafferentation produced by pronase injection into the sciatic nerve, true collateral sprouting of apparently uninjured saphenous central terminals occurs into the neighbouring sciatic nerve terminal territory (LaMotte et al, 1989;LaMotte and Kapadia, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…These neurons are able to regenerate after peripheral axotomy. The central projections of dorsal root afferents sprout after removal of adjacent dorsal roots (for review, see Murray, 1993) or after central denervation that partially denervates the dorsal horn (Murray and Goldberger, 1986). Dorsal root axons are also capable of regenerating into transplants of fetal tissue placed into the spinal cord after axotomy (Tessler et al, 1988) or after removal of their normal targets by excitotoxins (Nothias and Peschanski.…”
Section: Phosphorylated Maplb and Morphological Plasticity In The Adumentioning
confidence: 99%
“…Data from quantitative immunoelectron microscopy and receptor binding experiments showed that this change resulted from the degeneration of dorsal root afferents (17,18). In turtles, the dorsal root terminals were found in synaptic fields Ia, Ib, II and III, with some long fibers projecting to the contralateral dorsal horn (9).…”
mentioning
confidence: 99%